Oracle SQL*Plus : pocket reference - Gennick, Jonathan (O'Reilly, 2000)
This pocket reference provides quick reference information that will help you use SQL*Plus, Oracle's interactive query tool. It summarizes all of the SQL*Plus syntax, including the syntax for new Oracle8 i release 8.1.6 features. SQL*Plus is available at every Oracle site--from the largest data warehouse to the smallest single-user system--and it's a critical tool for virtually every Oracle user. Despite its wide use, few developers and DBAs know how powerful a tool SQL*Plus can be. This book boils down the most vital information from Gennick's best-selling book, Oracle SQL*Plus: The Definitive Guide, into an accessible summary. It concisely describes interacting with SQL*Plus, selecting data, formatting reports with SQL*Plus, and tuning SQL queries. It also contains quick references to the SQL*Plus commands and format elements. This book is an indispensable companion to O'Reilly bestselling book, Oracle SQL*Plus: The Definitive Guide, but it does not replace it; the larger book is truly the definitive guide, suitable for readers at all levels of expertise. The definitive guide describes the many tasks that SQL*Plus can perform, and provides a tutorial on many SQL*Plus topics. But this quick reference is an excellent, portable resource for readers who want a pocket-sized summary of SQL*Plus capabilities and a reminder of how to issue specific commands and formatting options for SQL*Plus. Table of Contents: Interacting with SQL*Plus Selecting Data Formatting Reports Tuning SQL SQL*Plus Format Elements SQL*Plus Command Reference.